First case of huge classic papillary thyroid cancer rupturing spontaneously leading to ischemic necrosis, perforation and inflammation of overlying skin: Case report and review of the literature - Abusabeib, Abdelrahman (Int J Surg Case Rep, 2021)
INTRODUCTION: Papillary thyroid cancer (PTC) is the commonest form of well-differentiated endocrine carcinoma. It is categorized into indolent and aggressive, where the indolent subtypes (classic, follicular) rarely demonstrate aggressive behavior. We present a classic PTC presenting with a rapidly growing huge anterior neck mass that subsequently spontaneously ruptured subcutaneously resulting in ischemia, necrosis, and perforation of overlying skin leading to inflammation. PRESENTATION OF CASE: A 37-year-old female with no comorbidities presented to our emergency department with a neck swelling of 2 years duration that rapidly enlarged one week prior to presentation. Though the mass initially appeared of inflammatory nature, the tumor was a PTC, and she underwent total thyroidectomy with selective right side neck dissection and debridement of necrotic skin. The gross specimen revealed a fragmented non-intact right thyroid lobe mass causing pressure ischemia, necrosis and perforation of the skin. Histopathology showed a 9 × 9 × 5 cm classic PTC staged as pT3b N1b. Postoperative course was uneventful, she was discharged by the eighth postoperative day, and then she received a high dose of radioactive iodine ablation (RAI). DISCUSSION: Classic PTC is usually of a smaller size and a relatively benign course compared to other PTC subtypes and thyroid cancers. It is indolent with favorable prognosis. Although it is associated with increased risk of lymph node metastases at the time of diagnosis, it is slow growing with high survival rates approaching 95%. CONCLUSION: Despite that classic PTC progresses slowly, it should still be suspected in neck swellings presenting with rapid and aggressive behavior. Prompt and systematic assessment is required with surgical intervention and radioactive iodine ablation therapy.